Agroecological environmental education: An integrated approach for the promotion of sustainability - Oliveira, Renata Aleixo de; Murata, Afonso (Seven Editora, 2023)
Agroecological environmental education emerges to break the paradigms of conventional environmental education. Emerging an approach that seeks the integration of the subject with the environment in which he is inserted, taking into account the preservation of the ecological environments that are part of the reality of the students. This perspective recognizes the importance of interaction between humans, nature and the agroecological system, promoting a broader and more meaningful understanding of the environment. This article aimed to reflect on a practical experience and the challenges encountered in the development of the agroecological environmental education project. The project was developed during the year 2022 at the Casemiro Karman State College in Campo Largo/PR. The school has the modality of integral education that provided educators, students, community and university to unite to develop collectively the project. The initial proposal was the construction of an agroecological garden, which expanded to soil restoration by carrying out processes such as composting and vermicomposting. Given the results obtained and the lessons learned throughout this project, we emphasize the importance of agroecological environmental education as an essential tool in the formation of a sustainable consciousness. This integrated approach, which considers the interaction between society, agriculture and the environment, is fundamental to promote environmental preservation, food security and the well-being of communities. DOI:https://doi.org/10.56238/ptoketheeducati-049